PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA ATAS RISIKO YANG TERJADI DALAM PERJANJIAN BERDASARKAN HUKUM PERDATA - Ratnasari, Vivi; Pasaribu, Agnes; Mulyanto, Rudi (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
Legal Protection Of Business Doors The Risk That Happened In The Agreement Based On Civil Law (Study at PT. Adi Putra Narasi, Denpasar City, Bali Province) and (Study at PT. Kurnia Bhakti Sejahtera Banyuwangi). Legal protection must be implemented in every country to be given to the people, of course in each country using different methods for legal protection of the people, especially Indonesia. In every business actor will face and get an unpredictable risk. Risk is a result that is unpleasant (harmful, harmful) from an action or action, either intentionally or unintentionally. In a business activity there is a cooperation agreement in carrying out a business activity. (a) What are the risks faced by Adi Putra Narasi Limited Liability Company in the cooperation agreement with Pertamina Patra Niaga Limited Liability Company in implementing non-subsidized fuel oil distribution activities and Elnusa Petrofin Limited Liability Company in the fuel/bbk transport tank rental agreement? (b) How is the legal protection for business actors for the risks that occur in the Adi Putra Narasi Limited Liability Company based on the Civil Code? This research method uses inductive qualitative data analysis techniques and an empirical juridical approach. Collecting data through interviews with Limited Liability Company business owners and several staff at the Adi Putra Narasi Limited Liability Company (PT) by documenting, direct observation in the field. Secondary data obtained through various sources such as books, journals, data from the internet and data needed in order to systematically identify the data.The results of this study conclude that (a) There are several risks faced by Adi Putra Narasi Limited Liability Company (PT) which include: the relatively high price of non-subsidized fuel oil; risk of meeting targets; risk of decreasing sales results; tank car maintenance and maintenance risks. (b) Based on the risks faced by business actors, of course they have not received legal protection in accordance with the Civil Code, listed in article 1365; 1233; 1244; 1245 of the Civil Code. According to the author, business actors have not been protected based on legal protection in accordance with all the risks experienced by business actors